SPECTRUM OF INFECTIOUS DISEASES AND ANTIBIOTIC USAGE IN A PAEDIATRIC OUTPATIENT DEPARTMENT - Alili-Idrizi, Edita; Malaj, Ledjan; Dauti, Merita (European Scientific Journal, ESJ, 2013)
The main objective of this study is to analyze the spectrum of infectious diseases in paediatric population and to study the antibiotic usage and selection of the dosage forms in children taking treatment in the outpatient department of the paediatric hospital in Tetovo. A retrospective study was undertaken during 01 January – 30 June of 2012. Drug data and patient characteristic data were computed using Ms. Excel 2007. Among the total number of 3778 patients analyzed during the period of six months, 1463 (38.7 %) of them were prescribed antibiotics, male patients were 829 (56.7%) and female patients were 634 (43.3 %). The majority of patients given antibiotics were aged >1 - ≤ 3 years (49.1 %). Incidence of infections was found to be 89.3% (1306 patients), of which upper respiratory tract infections (69.7%) were common among 1020 patients followed by lower respiratory tract infections in 234 (16.0%) cases. Cephalosporins were the commonest antibiotics prescribed (43.6%), among which cefaclor was the leading antibiotic prescribed in 283 (19.3 %) the total patients. Benzathine phenoxymethylpenicillin was the most common antibiotic prescribed in upper respiratory tract infections (23.8%) followed by cefaclor (19.7%). Syrups were the common dosage forms prescribed for all patients in the paediatric age group followed by capsules.